The Role of Counseling Teachers in Guiding Negative Behavior (Early Youth) of Grade IX Students Madrasah Tsanawiyah of Darunna'im - Ayu Auliya; Diah Nurul Fitriani; Dasril Dasril (Suluh: Jurnal Bimbingan dan Konseling, 2023)
Adolescence is a transitional period of development and growth faced by children aged 15/16 years due to various physical, social and emotional changes, all of which will cause anxiety and discomfort. As a result. This period is also known as a period full of storms and pressure, because teenagers must learn to adapt and accept all the changes that often cause emotional upheaval in them. If the activities carried out by adolescents with their peers are inadequate to meet the demands of their energy fluctuations, adolescents often release their excess energy in a negative direction. This can happen because the environment is often not in accordance with inner desires or expectations, so that a person feels disappointed due to an imbalance between expectations and reality. Therefore, individuals who are in their teenage years especially early adolescents, need adjustments to these changes in tasks and roles so that adolescents feel that they are accepted by the environment and can adapt well to situations of environmental expectations. And as a BK teacher, you have to properly guide early youth so that they have a directed future. So the purpose of this study is: 1) to know the various behaviors of early adolescents. 2) knowing the factors behind early adolescent behavior. 3) to know the role of the counseling teacher in guiding the behavior of early adolescents. In this research method using qualitative methods, all existing data were analyzed using interviews, observation, and documentation.